Macrophage apoptosis using alendronate in targeted nanoarchaeosomes - Jerez, Horacio Emanuel (2021)
Nanoarchaeosomes are non-hydrolysable nanovesicles made of archaeolipids, naturally functionalised with ligand for scavenger receptor class 1. We hypothesized that nitrogenate bisphosphonate alendronate (ALN) loaded nanoarchaeosomes (nanoarchaeosomes(ALN)) may constitute more efficient macrophage targeted apoptotic inducers than ALN loaded nanoliposomes (nanoliposomes (ALN)). To that aim, ALN was loaded in cholesterol containing (nanoARC-chol(ALN)) or not (nanoARC(ALN)) nanoarchaeosomes. Nanoarchaeosomes(ALN) (220–320 nm sized, ~ −40 mV ξ potential, 38–50 μg ALN/mg lipid ratio) displayed higher structural stability than nanoliposomes(ALN) of matching size and ξ potential, retaining most of ALN against a 1/200 folds dilution. The cytotoxicity of nanoARC(ALN) on J774A.1 cells, resulted > 30 folds higher than free ALN and nanoliposomes(ALN) and was reduced by cholesterol in nanoARC-chol(ALN). Devoid of ALN, nanoARC-chol was non-cytotoxic, exhibited pronounced anti-inflammatory activity on J774.1 cells, strongly reducing reactive oxygen species (ROS) and IL-6 induced by LPS. Nanoarchaeosomes bilayer extensively interacted with serum proteins but resulted refractory to phospholipases. Upon J774A.1 cells uptake, nanoarchaeosomes induced cytoplasmic acid vesicles, reduced the mitochondrial membrane potential by 20–40 % without consuming ATP neither damaging lysosomes and increasing pERK. Refractory to chemoenzymatic attacks, either void or drug loaded, nanoarchaeosomes induced either anti-inflammation or macrophages apoptosis, constituting promising targeted nanovesicles for multiple therapeutic purposes.